Potential of Genome Editing to Capture Diversity From Australian Wild Rice Relatives - Abdullah, Muhammad; Okemo, Pauline; Furtado, Agnelo; Henry, Robert (Frontiers in Genome Editing, 2022)
Rice, a staple food worldwide and a model crop, could benefit from the introduction of novel genetics from wild relatives. Wild rice in the AA genome group closely related to domesticated rice is found across the tropical world. Due to their locality outside the range of domesticated rice, Australian wild rice populations are a potential source of unique traits for rice breeding. These rice species provide a diverse gene pool for improvement that could be utilized for desirable traits such as stress resistance, disease tolerance, and nutritional qualities. However, they remain poorly characterized. The CRISPR/Cas system has revolutionized gene editing and has improved our understanding of gene functions. Coupled with the increasing availability of genomic information on the species, genes in Australian wild rice could be modified through genome editing technologies to produce new domesticates. Alternatively, beneficial alleles from these rice species could be incorporated into cultivated rice to improve critical traits. Here, we summarize the beneficial traits in Australian wild rice, the available genomic information and the potential of gene editing to discover and understand the functions of novel alleles. Moreover, we discuss the potential domestication of these wild rice species for health and economic benefits to rice production globally.